Vital (Johannine) Signs: Crip-tic' Enactments of a Man at the Pool (John 5:1-18) - Lawrence, Louise Joy (Biblical interpretation, 2019)
John 5:1-18 is here interpreted crip-tically' (through a crip hermeneutic) which seeks to pay due attention to the man at the pool and his enactments'. In order to subvert notions of what Alison Kafer has termed curative time', here this sign is seen to afford something other than a normalisation or physical healing of a body. Inspiration is drawn from two recent disability arts exhibits - Liz Crow's Bedding Out (2012-2013) and Noëmi Lakmaier's One Morning in May (2012) - and their respective illustrations of crip time and movement to highlight how the man in John 5:1-18 too has the potential to subversively refigure normative' understandings of time, space and embodiment within the Gospel.